Exploring the Discriminatory Potential of F0 Distribution Parameters in Traditional Forensic Speaker Recognition - Kinoshita, Yuko; Ishihara, Shunichi; Rose, Philip (International Journal of Speech, Language and the Law, 2009)
Despite its many prima facie attractive properties for Forensic Speaker Recognition, F0 is regarded as having limited forensic value due to its large within-speaker variability. However, its forensic use to date has been limited mostly to its long-term mean and standard deviation. This paper examines the discriminatory potential, within a Likelihood Ratio-based approach, of additional parametric features from the distribution of long-term F0: its skew, kurtosis, modal F0 and modal density. Motivated by the observation that the shape of the long-term F0 distribution shows less within-speaker occasion-to-occasion difference, we report a forensic discrimination experiment with non-contemporaneous speech samples from 201 male Japanese speakers. Using a multivariate Likelihood Ratio as discriminant distance with the six LTF0 distribution parameters, an equal error rate of 10.7% is obtained from 201 target and 80400 non-target trials. We also investigate how the EER degrades as a function of amount of voiced speech.